PERISTILAHAN RITUAL ADAT NGOJOK PADA MASYARAKAT DAYAK BANYADU - Daria, Evalisca; Amir, Amriani; Jupitasari, Mellisa (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
This study aims to describe the traditional rituals term "Ngojok" in the Dayak Banyadu community. The problem of this research is the form of terminology, lexical meaning, cultural meaning, grammatical meaning, and the implementation of the Ngojok customary ritual in the Dayak Banyadu community towards learning in schools. This research Uses a descriptive method in a qualitative form. Data collection techniques namely, observation techniques, interviews, note and record. This study produced 108 data on the terminology of the Ngojok customary ritual in the Dayak Banyadu community cosisting of 21 monomorphemic forms of data, 7 data of polymorphemic forms. Based on the lexical meaning there are 36 data, 12 data gramatical meaning, and 16 data cultural meaning. The form of the indonesian language learning text based on the terminology of the ngojok customary ritual in the Dayak Banyadu community is a desciptive text.